An exploratory study of patients' views about being at high-risk for breast cancer and risk management beliefs and intentions, before and after risk counselling: Preliminary evidence of the influence of beliefs on post-counselling prevention intentions. Issue 3 (March 2017) - Paquet, Lise; Simmonds, Lisa; Yang, Charles; Verma, Shailendra
Highlights: Risk management counselling does not alter beliefs about patients 'at-risk status. Women perceive their at-risk status as serious, chronic but controllable. Intentions favoring surveillance and lifestyle do not change after risk counselling. Chemoprevention intentions are weaker after risk counselling. Intentions strengths predicted by necessity/concerns beliefs about risk management. Abstract: Objectives: 1) To describe how women at high-risk for breast cancer (BC) perceive their at-risk status and the options available to manage this risk, before and after risk counselling; 2) to explore the contributions of pre-counselling demographic, clinical, cognitive and emotional factors to post-counselling risk management intentions. Methods: 58 of 173 eligible patients (34%) enrolled and were asked to fill surveys including measures of 1) subjective risk, 2) illness (being at high-risk for BC) and 3) treatment (surveillance, lifestyle modifications, and chemoprevention) cognitions, 4) BC fear and 5) future risk management intentions, prior to and 3 months after risk consultation. Results: 48 of 58 participants (83%) completed both surveys. Beliefs and emotions about their condition and its management were stable over time. Surveillance and lifestyle were associated with stronger intentions, higher perceived need, and lower concerns than chemoprevention (all ps <0.001). The strongest predictors of intentions strengths were the women's beliefs about the risk reduction methods, especially for lifestyle and chemoprevention (all ps <0.01). Conclusions: The findings emphasize the importance of patients' beliefs in risk management decisions. Practical implications: Patients' treatment beliefs appear to influence their choice of BC risk reduction strategies and should be discussed during risk reduction consultations.